2022
DOI: 10.1186/s12967-022-03638-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term neuromuscular consequences of SARS-Cov-2 and their similarities with myalgic encephalomyelitis/chronic fatigue syndrome: results of the retrospective CoLGEM study

Abstract: Background Patients with long-COVID often complain of continuous fatigue, myalgia, sleep problems, cognitive dysfunction, and post-exertional malaise. No data are available on EMG recording of evoked myopotentials (M-waves) or exercise-induced alterations in long-COVID patients, providing evidence of muscle membrane fatigue. Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) develops in more than half of patients after an infectious disease, particularly viral diseases. A large proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 24 publications
0
15
0
2
Order By: Relevance
“…If tolerated (but not otherwise), the patient should gradually increase the length and intensity of activity. However, as covered in a previous article in this series,1 worsening of symptoms following physical or mental activity is a common feature of long covid313940 and necessitates caution along with careful pacing, starting with low level gentle exercise. Some patients may require pharmacological measures in combination with conservative measures to engage in any physical activity 27…”
Section: What Non-drug Treatments Are Available?mentioning
confidence: 92%
“…If tolerated (but not otherwise), the patient should gradually increase the length and intensity of activity. However, as covered in a previous article in this series,1 worsening of symptoms following physical or mental activity is a common feature of long covid313940 and necessitates caution along with careful pacing, starting with low level gentle exercise. Some patients may require pharmacological measures in combination with conservative measures to engage in any physical activity 27…”
Section: What Non-drug Treatments Are Available?mentioning
confidence: 92%
“…The pathomechanisms behind post-COVID Syndrome (PCS), Post-acute sequelae of SARS-CoV-2 infection or long COVID, are not well understood, plausibly because the manifestations and causes are diverse and semantically diffuse, thus hampering comparative descriptive and mechanistic studies. Similar to post-SARS-syndrome reported after the SARS epidemic in [2003][2004] (12,13), many clinicians noticed that some prevailing symptoms of PCS were reminiscent of chronic fatigue syndrome (ME/CFS) (14)(15)(16)(17). This syndrome is entirely based on clinical criteria and exclusion of other diagnoses, plausibly consisting of different causal entities resulting in a similar phenotype, which is centered around a chronic fatigue aggravated by physical and/or mental activity and accompanied by other symptoms (e.g.…”
Section: Introductionmentioning
confidence: 67%
“…This is still a controversial question and needs further research to provide an exact answer. The clinical features between Long COVID and ME/CFS are highly similar, and both include persistent fatigue, sleep problems, muscle aches, cognitive dysfunction and post-exercise discomfort, and in an observational trial prior to the COVID-19 pandemic, Long COVID and ME/CFS patients showed the same biological characteristics of these symptoms [42]. It is because of the high degree of symptom similarity between post-COVID and ME/CFS that a causal relationship between them has been sought by scholars.…”
Section: Discussionmentioning
confidence: 95%